Stationary quality of water before the sustainable environmental cost relative to addition of biomarkers: Puno bay, Titicaca lake, Peru - Argota Pérez, George (2020)
Pollution of the Lake Titicaca's interior bay is one of the environmental concerns about this ecosystem where the search for new assessments for decision-making is a scientific challenge. The purpose of the study was to evaluate the stationary quality of water according to the relative sustainable environmental cost with aggregation of biomarkers: Puno Bay, Lake Titicaca, Peru. In the area of proximity to the effluents discharge by the Espinar oxidation lagoon of (15°51.073 / 69"59.729 at a depth of 1.8 m) dissolved oxygen, pH, total dissolved solids, electrical conductivity, Cu+, Zn+, Pb+, Fe+, Cd+, Al+, Cl-, NO3 - and NO2 - was measured. Likewise, the mean lethal concentration (LC50) in the species Gambusia punctata (Poey, 1854) was also evaluated. With all the measurements, the relative sustainable environmental cost with biomarker aggregation (COASORbiom) was determined. Dissolved oxygen or dissolved total solids were the physical-chemical parameters that did not meet the maximum permissible limit together with Cu+, Zn+, Cd+ and Al+ according to Supreme Decree No. 004-2017-MINAM. It was observed, lethal toxic sensitivity at low concentrations and in a short period of time (5:00 h) in G. punctata. The COASORbiom estimated was 0.54 meaning to be classified in the relative unsustainable resource category. It was concluded that the sampling area next the Espinar oxidation lagoon in the Puno Bay showed pollution of the water column, with high probability of negative environmental effects requiring, the efficient treatment of the discharged effluents.